Integrated rock physics models for improved 4D seismic monitoring of CO2 sequestration in Otway Basin, Australia - Wisman, Putri; Urosevic, Milovan; Dance, T. (EAGE, 2009)
We build a detailed rock physics model that links the rock and fluid properties with seismic properties and accounts for variations in reservoir quality, fluid saturations, and seismic resolution. This approach will increase the accuracy of the predicted changes in elastic properties of the reservoir rock by calibration of the down-hole petrophysical log with core sample data and ultrasonic measurements. The results indicate that Vp core saturated provide good agreement with Vp log measurement when the “effective” Kgrain is applied. Results also suggest that “effective” Kgrain may be used to represent the average mineralogy of the grains. A comparative analysis has also been performed incorporating the petrographic descriptions and geochemical analysis. The expected mineralogy derived from “effective” Kgrain and petrographic analyses are very close further confirming the model. This type of detailed rock physics analysis provides the capability to forecast more accurately the changes in the 4D seismic response during long-term CO2 storage at the site, and could be a useful tool for future storage sites with similarly challenging geophysical monitoring objectives.